Species composition and host range of predatory Coccinellids (Coleoptera) in Doon valley, Uttarakhand, India - Pramod Chandra Khanduri; Pushpendra Sharma (Environment Conservation Journal)
Coccinellid beetles play an important role in pest control, as these Coleopteran     insects voraciously feed on various insect pests. We conducted a comprehensive     survey to study the species composition and host range of predatory coccinellids for three consecutive years (Jan. 2021-Dec. 2023) in agricultural & forest areas of Doon Valley, Uttarakhand. In this study, 13 species of predatory coccinellids belonging to 11 genera of 4 tribes and 4 subfamilies were identified, viz., Coccinella septempunctata (Linnaeus), Coccinella transversalis (Fabricius), Brumoides suturalis (Fabricius), Chilocorus nigrita (Fabricius), Rodolia sexnotata (Mulsant), Cheilomenes sexmaculata (Fabricius), Megalocaria dilatata (Fabricius), Anegleis cardoni (Weise), Oenopia sauzeti (Mulsant), Propylea dissecta (Mulsant), Hippodamia variegata (Goeze), Harmonia eucharis (Mulsant), and Scymnus saciformis (Motschulsky). The host range of all 13 coccinellid species was also studied. The host range of coccinellids includes the various kinds of prey and their host plants. The host range of coccinellids varied significantly depending on various factors like the species, the prey availability, favorable environmental situations, and emulation with other predators.